2004
DOI: 10.1136/ard.2002.004655
|View full text |Cite
|
Sign up to set email alerts
|

Arthrographic joint distension with saline and steroid improves function and reduces pain in patients with painful stiff shoulder: results of a randomised, double blind, placebo controlled trial

Abstract: Objective: To determine whether arthrographic distension with a mixture of saline and steroid, in patients with painful stiff shoulder for at least 3 months, is better than placebo in improving function, pain, and range of motion at 3, 6, and 12 weeks. Methods: A randomised, placebo controlled trial with participant and outcome assessor blinding in which shoulder joint distension with normal saline and corticosteroid was compared with placebo (arthrogram). Outcome measures, assessed at 3, 6, and 12 weeks, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
125
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 34 publications
5
125
1
2
Order By: Relevance
“…0-9 in the case of a Likert 0-9 scale used to measure pain) to identify sequences whose mean equalled the mean reported in the trial of interest. Where the two means matched, the model calculated a SD; finally, the mean of these SDs was calculated and used in our analysis (two studies 42,43 ). The R code is presented in Appendix 3.…”
Section: Data Extractionmentioning
confidence: 99%
See 4 more Smart Citations
“…0-9 in the case of a Likert 0-9 scale used to measure pain) to identify sequences whose mean equalled the mean reported in the trial of interest. Where the two means matched, the model calculated a SD; finally, the mean of these SDs was calculated and used in our analysis (two studies 42,43 ). The R code is presented in Appendix 3.…”
Section: Data Extractionmentioning
confidence: 99%
“…A summary of study characteristics is reported in Table 42, with further details available in Appendix 6. All were full papers of studies conducted in Australia, 43 Denmark 84 and Norway 36 and published between 1998 and 2008. All were two-armed trials.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations